If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -3) = -9 Reorder the terms: 2(-3 + x) = -9 (-3 * 2 + x * 2) = -9 (-6 + 2x) = -9 Solving -6 + 2x = -9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 2x = -9 + 6 Combine like terms: -6 + 6 = 0 0 + 2x = -9 + 6 2x = -9 + 6 Combine like terms: -9 + 6 = -3 2x = -3 Divide each side by '2'. x = -1.5 Simplifying x = -1.5
| a+2a=.08 | | 15/x-2=9/x | | 7x+5=2(3x+12) | | l+4=-2 | | 7(x-2)=3x-2 | | 9-x+8=-6 | | 15=x+12 | | e+-43=-45 | | 4(b-5)+5b(8-6b)= | | 7x+3=2x+58 | | -16(t^2-361)=0 | | 0.3(3n-5)=0.4-0.2(n-7) | | (q-5)*2=10 | | 12xX=72 | | a-52=112 | | (q-8)*3=6 | | X^2=5x+8 | | c=15+4*9 | | c=15+4*8 | | c=15+4*7 | | x-10=70-7x | | (e+1)*5=10 | | c=15+4*50 | | 2(z+2)-5=7 | | X^2y+3xy+xy^2=0 | | 2x^2-4x^3+12x-6=0 | | 500x-x=300 | | -5x+5=6-4x | | 2+2x=4x-14 | | 3(0--16)= | | -6x+8=20-10x | | 3(1+x)=14-x |